Leveraging the 1:1 iPad approach for enhanced learning in the classroom. Issue 3 (3rd July 2018) - Retalis, Symeon; Paraskeva, Fotini; Alexiou, Aikaterini; Litou, Zoi; Sbrini, Theofili; Limperaki, Youla
ABSTRACT: Mobile technologies are integrated parts of our lives, and their use in educational settings could provide new, exciting opportunities for teaching and learning. The integration of the iPad in education, in particular, is thought to bring a paradigm shift and transform the twenty-first century classroom. However, as it is relatively new and experiences from pilot projects are just now beginning to surface, little concrete research on how it can be effectively adopted in the classroom and in other pedagogical activities exists. This raises the question of how to support students and teachers to realize the full potential of the 1:1 iPad approach. We followed the principles of action research in order to explore students', teachers' and parents perception of 1:1 iPad approach in the classroom. Towards this, we conducted a mixed-method research and combined quantitative and qualitative data. For the needs of this research, we employed a set of questionnaires, interviews and best practice lesson plans and performed descriptive and inferential statistical analysis. The results indicate that students are more positive with reference to the iPad being an excellent tool that helps them organize and understand the course. Our future work will embrace iPad's educational potential and emphasize on the design and implementation of orchestrated learning content.